Comparison of experimental approaches for seismic performance evaluation of bridge piers with high strength self-consolidating concrete towards practical engineering application. (15th September 2021) - Qu, Hongya; Wu, Chengjun; Li, Tiantian; Fu, Jixing; Wang, Zhiqiang
Highlights: Seismic performance of self-consolidating concrete bridge column is evaluated. Specimens are based on practical engineering application in high seismic region. Comprehensive experiment is performed including quasi-static and shake table tests. Results of unidirectional, bidirectional cyclic and shake table tests are compared. Nonlinear numerical models with improved bond-slip modeling approach are developed. Abstract: In this study, three different types of experimental approaches are carried out for the seismic evaluation of high strength self-consolidating concrete bridge columns in high seismic zone, including unidirectional quasi-static, bidirectional quasi-static and shake table tests. The 1/4-scale bridge column specimens are based on the practical engineering application of urban viaduct in high seismic region of northern China. The use of high strength self-consolidating concrete is to fulfill the demand of short construction time, high seismic resistance and harsh weather durability in the area. Based on the experimental results, it is found that similar damage progression is observed from all the tested specimens with concrete crush and longitudinal rebar buckling. Quasi-static cyclic tests tend to be more conservative but to overestimate the energy dissipation capacity and ductility, and the coupling effect from bidirectional loading cannot be ignored. In addition, nonlinear numerical models with improved bond-slip modeling approach are developed and calibrated by OpenSEES with the experimental data, where good agreement is achieved especially at early loading stage.